Sistematik Filogenetik Isolat-isolat Kapang Indigenous Indonesia sebagai Entomopatogen Kutu Sisik (Lepidoshapes beckii Newman) Hama Tanaman Jeruk - Suharjono, Suharjono; Marhendra, Agung P.W.; Triwiratno, Anang; Wuryantini, Susi; R, Lina Oktavia (Universitas Atma Jaya Yogyakarta, 2010)
Citrus fruits constitute a basic agricultural product in many countries. They are a source ofnational income, empowering labor market in rural zones and those surrounding urban areas,and in addition to being an important part of the diet. Insects are common problems to plantingof citrus. Purple Scale, Lepidosaphes beckii (Newman) is one of the destructive insect pests ofcitrus worldwide. The control of purple scale insects in citrus utilizes native natural enemiesincluding pathogens. Most known species of mould are pathogens of purple scale insect of citrus.The objective of this research was to study phylogenetic systematics of Indonesian indigenousmould isolates as pathogen on purple scale insect (Lepidoshapes beckii Newman) pest of citrusplants. Seven mould isolates derived from Purworejo, Brastagi, and Poncokusumo were showedpathogenic on purple scale insect. The fungal isolates were cultured on PDA. The DNA of fungalmaterial was isolated with Kit Prepman Ultra (Applied Biosystems). Nuclear ribosomal LargeSubunit 28S rDNA (LSU) was amplified using primers ITS1 and ITS4. Products of PCR werepurified and sequenced. Based on the 28S rDNA sequence, the result was showed that isolate ofPW ASG D4 was related to Gibberella moniliformis dx-12, PC ORG D4 was related to Gibberella sp.1893, PW ASG D2 was related to Gibberella moniliformis BZ070101, PW LB D2 was related toGibberella moniliformis 52, BRS D22 was related to Fusarium oxysporum DC-1-67, PWRJ I D4 wasrelated to Fusarium culmorum SQ070108, and BRS D23 was related to Aschersonia sp. Ag-11.